Measurement Distortion Analysis of Repetitive and Isolated Track Geometry Irregularities - Ágh, Csaba (Periodica Polytechnica Civil Engineering, 2021)
Track geometry measurements are essential for day-to-day activities of railway maintenance and play an important role in vehicle-track simulations. The generally applied forms of longitudinal level and alignment recordings do not reflect the real shape of the track. Both the versine measurement method and the band-pass filters according to European regulation cause significant amplitude modification and pattern change. In addition, the distortion behavior of repetitive and isolated defects is fundamentally different. In this contribution, simulated measurements of various reference shapes, which represent repetitive and isolated track deformations, were investigated. Comprehensive functions for amplitude change and for other distortion factors were developed with analytical and numerical methods. For chord measurements, rules were found for zero points and distortion-free ranges. Regarding the standardized filters, a significant amplitude reduction of isolated defects was observed in all wavelength ranges. Since derailment and track degradation depend not only on the amplitude of the defect, also the derivatives of the original and filtered forms of reference shapes were investigated and, as a new approach, the defect features called ’hypothetical additional force’, ’speed of hypothetical wheel lift-off’, ’hypothetical deterioration impulse’ and ’hypothetical deterioration energy’ were introduced.